3 - Rethinking East African Integration: From Economic to Political and from State to Civil Society: DOI: 10.4314/ad.v29i2.22193 - Ochwada , Hannington (Africa Development, 2004)
This essay takes cognizance of the fact that integration, which entails the establishment of some structural conformity, is an important variable in the process of development. It traces historical efforts at integrating East Africa since pre-colonial times, explaining the changing nature of social and economic relations. The paper argues that state-driven efforts to integrate Africa in the colonial and early post-independence period militated against local patterns of cooperation in the East African sub-region because these schemes emphasised economic development. In any renewed effort toward integration, the emphasis ought to be laid on political debates and the participation of civil society in new forms of integration. By allowing greater participation of individuals in sub regional constitutional amendments, the region could enhance regional citizenship, mutual co-existence and provide an impetus for greater economic development. Moreover, a bottom-up approach to the question of citizenship would guarantee self-respect and security among the peoples of the region, and also lead1 to long-term political and economic security.